Disability, Non-disability and the Politics of Mourning: Re-conceiving the 'we' - Anne McGuire (Disability Studies Quarterly, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> In December of2007, the Globe and Mail, one of Canada’s national newspapers, published a series of articles written by columnist Ian Brown. In the three part-series entitled, “The Boy in the Moon,” Brown narrates his life with his cognitively disabled son. This paper explores Brown's articles in relation to Judith Butler's (2004) "Violence, Mourning, Politics," and conducts an analysis of how cognitive disability is being enacted as "not quite a life" (34). This paper demonstrates how Brown’s articles tell the story of cognitive disability as a state of brokenness, some-thing that requires fixing. Significantly, when disability defies and/or resists fixing, it is discursively re-framed as a tragic loss. By attending to the making of disability in Brown’s articles, this paper is more broadly interested in how disabled and non-disabled bodies ('we') are being formed in and through social spaces.
Keywords: cognitive disability; non-disability; interpretive methods; cultural studies; disability studies; relationality; governmentality; mourning